2013
DOI: 10.1117/12.2016639
|View full text |Cite
|
Sign up to set email alerts
|

Measure of decoherence in quantum error correction for solid-state quantum computing

Abstract: We considered the interaction of semiconductor quantum register with noisy environment leading to various types of qubit errors. We analysed both phase and amplitude decays during the process of electron-phonon interaction. The performance of quantum error correction codes (QECC) which will be inevitably used in full scale quantum information processors was studied in realistic conditions in semiconductor nanostructures. As a hardware basis for quantum bit we chose the quantum spatial states of single electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The described physical implementation of quantum walks has several advantages for quantum computing. One of them is that semiconductor charge qubits can be protected from computational errors 28,29 with the help of standard quantum error correction algorithms, 30,31 and by using a decoherence-free subspace qubit encoding. 32 In a single electron regime of the described quantum system, the electron spreads coherently which corresponds to a quantum walk dynamics of a single particle, 33 as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The described physical implementation of quantum walks has several advantages for quantum computing. One of them is that semiconductor charge qubits can be protected from computational errors 28,29 with the help of standard quantum error correction algorithms, 30,31 and by using a decoherence-free subspace qubit encoding. 32 In a single electron regime of the described quantum system, the electron spreads coherently which corresponds to a quantum walk dynamics of a single particle, 33 as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( 17) leads to errors in quantum information stored in the system of electrons. In order to quantify this error we use the measure of decoherence [22,54]…”
Section: B Electrons For Quantum Information Processingmentioning
confidence: 99%
“…Quantum dots in semiconductors can be used as building blocks for a construction of a quantum computer, where quantum dots positions provide a spatial degree of freedom of a quantum particle [17][18][19][20]. It was shown that a spatial location of an electron in one of two semiconductor quantum dots can serve for encoding a qubit [17,18] and errors that occur mostly because of the interaction * melnikov@phystech.edu † leonid@phystech.edu with acoustic phonons can be corrected [21,22]. In this paper we study quantum dots arranged in a circle, where each quantum dot can be populated by no more than one electron.…”
Section: Introductionmentioning
confidence: 99%